A novel id-iri score: development and internal validation of the multivariable community acquired sepsis clinical risk prediction model - Diktas, Husrev; Uysal, Serhat; Erdem, Hakan; Cag, Yasemin; Miftode, Egidia; Durmus, Gul; Ulu-Kilic, Ayşegul; Alabay, Selma; Szabo, Balint Gergely; Lakatos, Botond; Fernandez, Ricardo; Korkmaz, Pinar; et al. (Springer Science and Business Media LLC, 2020)
We aimed to develop a scoring system for predicting in-hospital mortality of community-acquired (CA) sepsis patients. This was a prospective, observational multicenter study performed to analyze CA sepsis among adult patients through ID-IRI (Infectious Diseases International Research Initiative) at 32 centers in 10 countries between December 1, 2015, and May 15, 2016. After baseline evaluation, we used univariate analysis at the second and logistic regression analysis at the third phase. In this prospective observational study, data of 373 cases with CA sepsis or septic shock were submitted from 32 referral centers in 10 countries. The median age was 68 (51-77) years, and 174 (46,6%) of the patients were females. The median hospitalization time of the patients was 15 (10-21) days. Overall mortality rate due to CA sepsis was 17.7% (n = 66). The possible predictors which have strong correlation and the variables that cause collinearity are acute oliguria, altered consciousness, persistent hypotension, fever, serum creatinine, age, and serum total protein. CAS (%) is a new scoring system and works in accordance with the parameters in third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3). The system has yielded successful results in terms of predicting mortality in CA sepsis patients.
Keywords: sepsis; mortality; community acquired; scoring system; sepsis-3